2018
DOI: 10.1097/ta.0000000000001989
|View full text |Cite
|
Sign up to set email alerts
|

Time to stroke: A Western Trauma Association multicenter study of blunt cerebrovascular injuries

Abstract: Prognostic/Epidemiologic, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
22
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 29 publications
3
22
1
2
Order By: Relevance
“…Our median time to stroke was 2.0 days, with a range of 0-12 days. This is similar to prior studies by Burlew et al (21) and Cothren el al (15), in which median times to stroke were 2.0 days (range, 0-46 days) and 2.1 days (range, 0-10 days), respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Our median time to stroke was 2.0 days, with a range of 0-12 days. This is similar to prior studies by Burlew et al (21) and Cothren el al (15), in which median times to stroke were 2.0 days (range, 0-46 days) and 2.1 days (range, 0-10 days), respectively.…”
Section: Discussionsupporting
confidence: 91%
“…The key findings are that BCVI and acute stroke are relatively common in trauma patients, and two thirds of acute strokes are present on admission. This proportion is higher than reported in “Time to Stroke,” a recent multicenter study, which found that stroke was present on admission in only one third of patients with BCVI 1 . However, this study did not consistently use MRI to diagnose stroke and did not use a universal CTA screening strategy across all centers.…”
Section: Discussioncontrasting
confidence: 57%
“…38,48,55 In addition, AP agents carry a theoretical advantage in that the mechanism of stroke in BCVI is typically artery-to-artery embolism, and AP agents are argued to be more appropriate in this pathophysiological context. 65 In their multicenter study reviewing BCVI stroke timing, Burlew et al 45 found that in patients who sustained stroke on treatment, twice as many patients were on AP agents versus anticoagulation. However, they did not collect information on all patients with BCVI; thus, the actual percentage of patients treated with AP agents versus systemic heparin could not be determined.…”
Section: Discussionmentioning
confidence: 99%
“…We could not carry out statistical analysis for radiographic progression rates and overall functional outcomes, but these outcomes appeared similar between the two groups. In the largest study of BCVI patients who suffered from stroke, Burlew et al 45 reported that 63 (51.6%) of 122 patients treated with APs and 70 (63.1%) of 111 patients treated with anticoagulation agents had neurologic improvement, when the different types of AC or AP therapies were pooled. 45 This suggests that anticoagulation therapy with heparin may be preferable in patients who have already suffered from a stroke, in terms of secondary prevention and improving overall clinical outcome.…”
Section: Discussionmentioning
confidence: 99%